Evaluation of low dose prazosin for PTSD-associated nightmares in children and adolescents - Nancy Hudson, PharmD; Steven Burghart, DPh, RPh, MBA, BCPP; Jill Reynoldson, PharmD, BCPP, DPLA; Dennis Grauer, MS, PhD (American Association of Psychiatric Pharmacists, 2023)
Introduction: Knowledge about fundamental sleep disorders and dysregulation that occurs in children with PTSD is limited. Prazosin is an alpha-1 receptor antagonist often used off label for the treatment of PTSD-associated nightmares in adults; however, evaluation of its use in pediatrics and adolescents is limited. The primary objective of this study was to assess the impact of prazosin on nightmares associated with PTSD in this population. Secondary objectives included assessing side effects, changes in blood pressure, and 30-day readmission rates. Methods: This was a retrospective, single-center chart review of inpatients diagnosed with PTSD nightmares from January 1, 2017, to July 31, 2019. Patients 4 to 18 years old with a PTSD diagnosis, experiencing nightmares, and initiating any dose of prazosin were assessed to determine efficacy and tolerance. Results: Forty-two patients were evaluated to determine symptom improvement after initiation of prazosin for PTSD nightmares in children and adolescents. Of the 42 patients, 24 (57.1%) reported improvement in nightmares (average dose 1.05 mg). For secondary results, 38 (90.5%) patients continued prazosin at discharge, and 2 (5%) were readmitted within 30 days for reasons other than PTSD-associated nightmares. Thirty-four (81%) reported having no adverse effects to prazosin. There was no significant difference in systolic (P =.1883) or diastolic (P = .2777) blood pressure preinitiation and postinitiation of prazosin. Discussion: Despite the limitations of this retrospective study, the data suggests that prazosin may be associated with an improvement in nightmares in children and adolescents with PTSD. Adverse events were rarely reported, and there was no significant change in blood pressure with initiation of prazosin.